Formação de produtos proteicos de oxidação avançada a partir da reação de fenton e colágeno: efeitos sobre processos inflamatórios em neutrófilos e células renais embrionárias - Bochi, Guilherme Vargas (2016)
The advanced oxidation protein products (AOPPs) are a new class of compounds identified as markers of oxidative damage to proteins. The physiology role of these products is not limited to assess the oxidative stress, and these products may actively participate in the inflammatory process, promoting different cell disorders, including induction of apoptosis and alterations in the processes of cell proliferation and differentiation. Myeloperoxidase (MPO)-derived hypochlorous acid (HOCl) produced by activated neutrophils contribute significantly to AOPP formation, and human serum albumin (HSA) is considered the main protein responsible for the generation of AOPPs However, the molecular composition of AOPPs is unclear. Additional pathways and protein targets for AOPP formation are largely unknown. The aim of this study was to induce the formation of AOPPs in vitro through Fenton reaction and to investigate whether this generation could be counteracted by N-acetylcysteine (NAC) and fructose-1,6-bisphosphate (FBP). In addition, this study aimed to examine whether AOPPs produced by Fenton reaction may induce the activation of the gene transcription of inflammatory molecules, including the nuclear factor-κB (NF-κB), cyclooxygenase-2 (COX-2) and interleukin-6 (IL-6) in human embryonic kidney cells (HEK 293). Additionally, it was investigated the collagen as a potential source of AOPPs via its exposure to HOCl. The HOCl-modified collagen stimulated the production of oxidants, such as HOCl and superoxide anion radical (O2 -), and pro-inflammatory agents, such as nitric oxide (NO) and AOPPs in human neutrophil. Furthermore, HOCl-modified collagen induced a decrease in cell viability and an increase of apoptosis in these cells. Finally, alpha-tocopherol inhibited the release of oxidants, decreased cell viability and apoptosis, suggesting a therapeutic potential means to prevent deleterious effects caused by AOPPs. Furthermore, these findings indicate that alternative pathways can form AOPPs, and these new products may contribute to the pathogenesis of several clinical conditions related to the accumulation of AOPPs.